Aktualisasi Paham Ahlussunnah Wal Jamaah Masyarakat Hollo Maluku Tengah di Dalam Penguatan Pendidikan Agama Islam - Moch. Irfan Syahroni; Muhammad Rofiq (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the actualization of Aswaja understanding in strengthening Islamic religious education within the Hollo community in Central Maluku. A qualitative approach with a case study method was employed to understand the process of internalizing Aswaja values, which underpin community life. Data were collected through in-depth interviews, observations, and documentation from religious leaders, families, and community members. The findings indicate that the application of Aswaja values extends beyond formal religious practices and is reflected in the community’s social and cultural structures. Religious figures and families play crucial roles in maintaining the continuity of these values through cultural approaches and personal communication, effectively instilling tolerance, moderation, and balance in daily life. Despite facing challenges such as globalization and limited educational infrastructure, the Hollo community has adapted by strengthening social solidarity and leveraging culturally based dakwah innovations. The organic model of Aswaja practice rooted in local traditions demonstrates the sustainability of moderate Islamic practices and their relevance within a pluralistic society. This study underscores the importance of developing contextual and sustainable Islamic education to reinforce a moderate Islamic identity in multicultural, non-boarding community settings